Lactate and lactylation in liver diseases: energy metabolism, inflammatory immunity and tumor microenvironment - Cheng, Shiyi; Xiao, Xiaoyu; Wang, Dingye; Wang, Xiyuan; Yang, Minlan (Frontiers in Immunology, 2025)
Liver diseases pose a significant threat to human health. Lactate, a byproduct of glycolysis, serves various biological functions, including acting as an energy source, a signaling molecule, and a substrate for lactylation. Lactylation is a novel lactate-dependent post-translational modification that plays a role in tumor proliferation, the regulation of immune cell function, and the modulation of gene expression. In this paper, we summarize the roles of lactate and lactylation in energy metabolism, inflammatory immunity, and the tumor microenvironment, while also elucidating recent research advancements regarding lactate and lactylation in the context of hepatic fibrosis, non-alcoholic fatty liver disease, and hepatocellular carcinoma. Furthermore, lactate and lactylation are proposed as promising new targets for the treatment of liver diseases.